Optimalisasi Desa Wisata Berbasis UMKM Melalui Destination Branding - Perguna, Luhung Achmad; Irawan, Irawan; Tawakkal, Muhammad Iqbal; Mabruri, Diva Avivi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The development of Small, Micro and Medium Enterprises (MSMEs) is one of the driving forces of the community's economy, especially in villages. Unfortunately, the potential of MSMEs scattered in this village is not yet utilized optimally by the village. Optimizing can be done in many ways, one of them by building village destination branding. The construction and design of destination branding is carried out in Gogodeso village, Blitar district which has many potential MSMEs to be developed, unfortunately not yet communicated by the local community and government optimally. Destination branding is the answer in overcoming it. The stages of destination branding development go through five steps namely market analysis, brand identity, brand recognition, brand implementation and finally launching. The process of developing video-based destination branding is part of the vision and identity of the village of Gogodeso aimed at changing the perception of the village of Gogodeso. As a result, the village's identity as a tourist village of UMKM began to be formed in the public through videos and websites that are spread and socialized in the village community.